A single case training study: influence of living low training high on aerobic power for a top class handy bike athlete - de Marees, M.; Hein, M.; Abel, T.; Mester, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Despite the fact that hypoxic training is a well-accepted training intervention by elite athletes to increase their performance under normoxic conditions there is still an ongoing controversy debate about the effectiveness of hypoxic exposure. By training under hypoxic conditions an additional lowered oxygen level in the musculature will occur to offer a much stronger stimulus which in turn will induce a greater adaptation and therefor a rise in performance capacity. But the most efficient training design to ensure the best increase in performance is still uncertain. Especially adaptations induced by the living low training high (LL-TH) method are at least doubtful (Lundby et al. 2012). However we will show the effect of a training camp at sea-level in comparison to a LL-TH intervention